Onychomycosis: Potential of Nail Lacquers in Transungual Delivery of Antifungals - Nida Akhtar; Hemlata Sharma; Kamla Pathak (Scientifica)
Onychomycosis constitutes the most common fungal infection of the nail (skin beneath the nail bed) that affects the finger as well as toe nails. It is an infection that is initiated by yeasts, dermatophytes, and nondermatophyte molds. Nail lacquers are topical solutions intended only for use on fingernails as well as toenails and have been found to be useful in the treatment of onychomycosis. Thus, in the present review an attempt has been made to focus on the treatment aspects of onychomycosis and the ungual delivery of antifungals via nail lacquer. Several patents issued on nail lacquer till date have also been discussed. Penetration efficiency was assessed by several researchers across the human nail plate to investigate the potentiality of nail lacquer based formulations. Various clinical trials have also been conducted in order to evaluate the safety and efficacy of nail lacquers in delivering antifungal agents. Thus, it can be concluded that nail lacquer based preparations are efficacious and stable formulations. These possess tremendous potential for clinical topical application to the nail bed in the treatment of onychomycosis.